PEMILIHAN PROMOSI JABATAN KARYAWAN DENGAN METODE FUZZY C-MEANS DAN METODE AHP - Agus Suryadi (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
Employee performance is one of the factors that can determine the good or bad running of a company. A company generally has employees who occupy a number of positions or positions, be it at the staff level or section head. Promotion as one of the functions of human resource management activities has a very important role in increasing employee productivity. Promoting employees requires careful consideration, especially for middle and upper positions. To get a promotion in a company, of course there is a process of selecting employees who have met the criteria and requirements. Company xyz still uses manual methods in the process of selecting qualified employees to get promotions. Fuzzy C-Means (FCM) is one of the most frequently used clustering methods. However, FCM has some drawbacks such as the number of clusters to be predefined and the partition matrix to be random starting which makes the clustering results inconsistent. Analytical Hierarchy Process (AHP) can help solve problems into a hierarchical structure consisting of objective criteria and sub-criteria. This study aims to combine the two methods in the selection of promotions and implement these methods into a web-based decision support system. Keywords - promotion, Fuzzy C-Means method, AHP method